Development of Integrated Audiovisual Digital Handout Through Flipbook Application Based on Realistic Mathematics Education - Fajriana, Fajriana; Mahmuzah, Rifaatul; Ningtiyas, Fitri Ayu; Sinaga, Nurul Afni; Aufa, Zurra Yusally; Saragih, Novilia Junianti (International Journal of Engineering, Science and Information Technology, 2025)
Effective learning media that prioritizes digitalization in the learning process and curriculum development are needed to improve students' numeracy literacy skills. One type of digital learning media is digital handouts, which are expected to provide positive changes in the world of education. Digital learning media that prioritizes audiovisual is expected to provide new learning experiences for students. This study will determine whether students' numeracy literacy skills increase after studying digital audiovisual handouts through the Realistic Mathematics Education-Based Flipbook Application. This research method uses the modified Borg and Gall model with stages of needs analysis, planning, initial product development, initial field trials, revision of test results, field trials of the main product, product revision, and final product and implementation. The research was conducted at SMPN 1, SMPN 2, and SMPN 3 Dewantara. The subjects of this study were students of grade VIII. The object of the research was Integrated Audiovisual Digital Handouts Assisted by Flipbook Application Based on Realistic Mathematics Education. The results of the validity test by material experts and media experts showed that the media that had been developed was feasible to be tested on students. The results of the small group trial stated that the press created was valid in appearance, ease of use, and usefulness so that it could be used in the media effectiveness trial through evaluation.